FEATURES OF SYNCHRONOUS AND ASYNCHRONOUS E-LEARNING ON THE EXAMPLE OF TEACHING THE EUROPEAN EXPERIENCE OF SOCIAL INCLUSION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The research focusing on synchronous and asynchronous learning is often reduced to a psychological assessment of the learner. The learner's motivation will determine the success of the learning process. The quality of perception and understanding of the educational content offered will depend on their experience. Familiarity with the research of the international community and European practices allowed us to select interesting content and diversify the module "Social integration of children with special needs in an environment of diversity and inclusion: European approaches" (SEEDUE4UA-101085267), as well as supplement the content of related disciplines. However, we paid most attention to the issue of synchronous and asynchronous format of the online educational process. We had to implement this aspect of interaction with students due to the consequences of military aggression in Ukraine. And for the convenience of both students and teachers, we created a flexible package of educational content that allowed us to engage young people through the use of video materials, individual and group projects, and quickly change the form of the online classroom (when the lesson began in the synchronous mode of group interaction, and after 20-30 minutes we had to interact with students asynchronously due to the danger to the life and health of the participants in the educational process). The biggest challenge in the flexible format for our team was the development of emotional intelligence, that is, the ability of students to assess the situation in an inclusive educational environment, conduct supervision, lead a discussion, etc. Among the challenges, we also considered the issue of implementing sections of changes in students' attitudes and perceptions of information as a result of mostly asynchronous interaction. That is why, in the course of this scientific review, we analysed the forms of interactive interaction we selected, described some of the programmes that were used and involved students with appropriate reflection with elements of simulation games, etc. We also drew an analogy with certain topics studied by full-time students in the traditional offline mode of interaction. This allowed us to draw conclusions about the need to adjust certain elements of the programme for all forms of the educational process based on the results of reflection on certain elements of emotional intelligence development within the framework of simulations of physiological and social skills. As we noted earlier, this analysis allowed us to revise the amount of material and the format of its presentation for better mastering the module issues, as well as to develop a universal toolkit that can be flexibly used in the process of mastering information on social inclusion and European experience in synchronous and asynchronous formats of both project implementation and teaching of relevant disciplines.